Combined liver transplantation and off-pump coronary artery bypass grafting: A report of two cases - Uludağ Yanaral, Tümay; Ertuğrul, Gökhan; Ulukan, Mustafa Özer; Karaaslan, Pelin; Karaca, İbrahim Oğuz; Dayangaç, Murat (Taylor & Francis Ltd, 2022)
Introduction: Liver transplantation (LT) is the most effective treatment modality in patients with end-stage liver disease (ESLD). With the increased prevalence of diabetes and non-alcoholic fatty liver disease (NAFLD), coupled with a steady increase in the age of transplant population, liver transplant candidates are at increased risk for coronary artery disease (CAD). Improvements in anesthesia, surgical experiences, and increased effectiveness of drugs have facilitated concurrent surgical interventions in transplantation, allowing for orthotopic LT to be performed in elderly patients with a high incidence of coexisting diseases, especially those of the cardiovascular system. In this study, we present two cases of combined off-pump coronary artery bypass surgery and living donor liver transplantation. Case presentation: A 68-year-old male patient with ESLD due to chronic hepatitis C infection and multi-vessel CAD, and a 65-year-old female patient with NAFLD cirrhosis and multi-vessel CAD were referred to our institution for an LT evaluation. We performed combined living donor LT and off-pump coronary artery bypass surgery in both patients. Both the first and second patients were alive with good liver and cardiac function at the 25 and 15 months after surgery, respectively. Conclusion: Combined off-pump coronary artery bypass surgery and living donor LT are an alternative treatment for patients with severe CAD and ESLD. We consider that combined coronary artery bypass graft surgery and LT can be safely performed by experienced anesthesia and surgical teams in selected patients.
Keywords: Anesthesia; Coronary Arterybypass; Coronary Arterydisease; End Stage Liverdisease; Livertransplantation